Synthesis, characterization, conduction, and dielectric properties of tetra tert-butylsulfanyl substituted phthalocyanines - Kaipova, Saida; Dincer, Hatice; Altindal, Ahmet (TAYLOR & FRANCIS LTD, 2015)
The tert-butylsulfanylphthalonitrile has been prepared with optimized synthetic procedure. Metal free (H2Pc) and metallo phthalocyanines (Pcs) (ZnPc, CoPc, CuPc, PbPc) have been synthesized by cyclotetramerization of tert-butylsulfanylphthalonitrile in the presence of DBU and metal salts. Thus, tert-butylsulfanyl groups enhance the solubility, shift the Q band absorption to the red visible region, and inhibit efficient cofacial interaction of the Pcs (2-6) as evaluated by UV-vis spectra. The electrical conduction and dielectric properties of the synthesized Pc thin films sandwiched between indium tin oxide and aluminum electrodes (ITO-Pc-Al) were investigated from 300 to 500K. At low bias voltage the conduction is ohmic while at high bias voltage the conduction becomes space charge limited with an exponential distribution of traps. The measured ac conductivity data are discussed in terms of classical models based on pair approximation. It was found that the ac conductivity obeys the power law given by sigma(ac) = sigma(s)(0), in which the frequency exponent s decreases with temperature. The real and imaginary parts of the impedance are found to be dependent on both frequency and temperature.
Keywords: Tert-butylsulfanyl; Phthalonitrile; Phthalocyanine; Conduction; Dielectric properties; ZINC PHTHALOCYANINE; COPPER PHTHALOCYANINE; ELECTRONIC-STRUCTURE; AGGREGATION; CURRENTS; Chemistry